2016
DOI: 10.1038/nrneph.2016.168
|View full text |Cite
|
Sign up to set email alerts
|

The epigenetic landscape of renal cancer

Abstract: | The majority of kidney cancers are associated with mutations in the von Hippel-Lindau gene and a small proportion are associated with infrequent mutations in other well characterized tumour-suppressor genes. In the past 15 years, efforts to uncover other key genes involved in renal cancer have identified many genes that are dysregulated or silenced via epigenetic mechanisms, mainly through methylation of promoter CpG islands or dysregulation of specific microRNAs. In addition, the advent of next-generation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
111
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(117 citation statements)
references
References 245 publications
(285 reference statements)
1
111
0
Order By: Relevance
“…Early diagnosis of the disease is difficult, and metastases often occur before the primary tumor is detected. Therefore, radical nephrectomy is considered to be the most effective way to treat ccRCC [9, 10]. But the five-year survival rate for individuals with metastatic disease is still less than 10% [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early diagnosis of the disease is difficult, and metastases often occur before the primary tumor is detected. Therefore, radical nephrectomy is considered to be the most effective way to treat ccRCC [9, 10]. But the five-year survival rate for individuals with metastatic disease is still less than 10% [11].…”
Section: Introductionmentioning
confidence: 99%
“…But the five-year survival rate for individuals with metastatic disease is still less than 10% [11]. It has been reported that hepatocyte growth factor (HGF) binding to its receptor, tyrosine-protein kinase Met, leads to activation of the Ras/MAPK signaling pathway to promote ccRCC growth and metastasis [9, 12]. Function of the RAS-Mitogen activated protein kinase (MAPK) signaling pathway (also known as the RAS-RAF-MEK-ERK pathway) is to integrate extracellular signals and to coordinate a suitable response by a subsequent control of cellular growth, survival, and differentiation[13].…”
Section: Introductionmentioning
confidence: 99%
“…It leads to gene silencing and contributing to carcinogenesis and development of cancers . Thus, detection of aberrant gene promoter methylation in biopsy specimens and noninvasive body fluids, like serum, has been widely used for diagnosis of different tumors, such as lung cancer, breast cancer, gastric cancer, renal cancer, and NPC . As a nonnegligible gene related to initiation and invasion of cancers, aberrant methylation of the E‐cadherin gene, which leads to E‐cadherin silencing, is also detected in NPC…”
Section: Introductionmentioning
confidence: 99%
“…This is illustrated by the relative high frequency of promoter methylation as compared to the number of somatic alterations in RCC [14]. Furthermore, in contrast to somatic mutations in RCC, DNA methylation alterations are often shown to be associated with clinicopathological features and patient survival [14,15]. DNA methylation consists of the covalent addition of a methyl group to cytosines that precede a guanosine, the CpG dinucleotide, which are mainly clustered as CpG islands in the promoter region of genes [13].…”
Section: Introductionmentioning
confidence: 99%